THE INFLUENCE OF DESTINATION IMAGE AND TOURIST SATISFACTION TOWARD REVISIT INTENTION OF SETU BABAKAN BETAWI CULTURAL VILLAGE - Wibowo, Setyo Ferry; Sazali, Adnan; Kresnamurti R. P., Agung (JRMSI - Jurnal Riset Manajemen Sains Indonesia, 2016)
The purpose of this research are: 1) To find out the description of destination image, tourist satisfaction, and revisit intention of Betawi cultural village Setu Babakan, 2) test empirically the influence of destination image toward revisit intention of Betawi cultural village Setu Babakan, 3) test empirically the influence of tourist satisfaction toward revisit intention of Betawi cultural village Setu Babakan, 4) test empirically the influence of destination image toward revisit intention of Betawi cultural village Setu Babakan. The object of this research was 200 respondents who have ever visit to Betawi cultural village Setu Babakan at one time. The results of descriptive test explained that the destination image provided is good according to the tourist, so that the tourist is satisfied and want to revisit intention of Betawi cultural village Setu Babakan. The hypothesis test shows: 1) the influence of destination image toward revisit intention by -30%, 2) the influence of tourist satisfaction toward revisit intention by 118%, 3) the influence of destination image toward tourist satisfaction by 92%. Keywords: destination image, tourist satisfaction, revisit intention, Setu Babakan Betawi cultural village